1947
DOI: 10.1029/tr028i002p00285
|View full text |Cite
|
Sign up to set email alerts
|

A determination of the effect of topography upon precipitation

Abstract: This paper describes a graphical correlation technique for relating mean winter precipitation in western Colorado to the topographic parameters; elevation, maxi mum slope of the land, exposure, and orientation. This is done by obtaining graphically values of precipitation as a function of elevation for various values of slope. Relating these values with orientation and thence exposure, a set of working charts is obtained. A high degree of correlation is shown to exist between the observed values of precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 2 publications
2
68
0
4
Order By: Relevance
“…Previous studies have shown that precipitation patterns are more highly correlated with broad-scale topographic features than with local features (e.g. Spreen, 1947;Burns, 1953;Schermerhorn, 1967;Daly et al, 1994;Kyriakidis et al, 2001). Many of these studies and results from other PRISM modelling activities suggest that 2.5 is near the optimum resolution for modelling precipitation.…”
Section: Elevation Datamentioning
confidence: 99%
“…Previous studies have shown that precipitation patterns are more highly correlated with broad-scale topographic features than with local features (e.g. Spreen, 1947;Burns, 1953;Schermerhorn, 1967;Daly et al, 1994;Kyriakidis et al, 2001). Many of these studies and results from other PRISM modelling activities suggest that 2.5 is near the optimum resolution for modelling precipitation.…”
Section: Elevation Datamentioning
confidence: 99%
“…Relatively high levels of correlation have been identified; the relationship is generally an increasing one (Spreen 1947;Arora et al, 2006): as elevation increases, precipitation increases. This is mainly due to the 'orographic effect' of the mountain terrain.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have relied on establishing a correlation between precipitation and elevation to improve our understanding of precipitation patterns (Spreen, 1947;Daly et al, 1994;Pardo-Iguzquiza, 1998;Goovaerts, 1999aGoovaerts, , 1999bGoovaerts, , 2000KiefferWeisse and Bois, 2001;Marquinez et al, 2003;Kyriakidis et al, 2004;Arora et al, 2006). Relatively high levels of correlation have been identified; the relationship is generally an increasing one (Spreen 1947;Arora et al, 2006): as elevation increases, precipitation increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The orographic effect may be the reason to increase the parameters A in the high altitude zone. The rainfall intensity can be increased due to the ascending air current following the mountain slopes, which can also be strengthened when the humidity and wind velocity are all high [26][27][28][29][30][31].…”
Section: Parameter Estimation Of Z-r Relationmentioning
confidence: 99%